Best Answer

Do you mean like:

(ax +b)(cx+d) = 0

For the LHS (Left Hand Side) to be zero, either (or both) of the brackets must be zero, that is:

ax+b = 0 or cx+d = 0

which can be solved quite simply by rearranging them:

ax+b=0 -> x = -b/a

cx+d=0 -> x = -d/c

So the solution would be x = -b/a or x = -d/c.

If this is not what you mean, ask again giving an example.

Perhaps, despite being correct, you may be over thinking this. The contributor may mean simply what is meant by two sets of brackets next to each other. In which case the answer is: The results of the pair of brackets are multiplied together.

Q: How do you solve an equation with brackets side by side?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Like what?

Divide each side of the equation by 10 .

factorise it into brackets. The equation is actually x2-6x+0. So into brackets it will be (x-6)(x+0) = 0. From here, to solve the equation, make either of the brackets = 0 by substituting a value for x. In this instance x = 0 or 6.

You solve just like any other equation: You try to manipulate your equation so that the "x" is alone on the left side, and everything else on the right side.

2nd [CATALOG], solve( , enter equation, variable and guess after the bracket, close brackets with " ) ". You can also put lower and upper bounds after the guess.

Related questions

Like what?

Divide each side of the equation by 10 .

factorise it into brackets. The equation is actually x2-6x+0. So into brackets it will be (x-6)(x+0) = 0. From here, to solve the equation, make either of the brackets = 0 by substituting a value for x. In this instance x = 0 or 6.

You solve just like any other equation: You try to manipulate your equation so that the "x" is alone on the left side, and everything else on the right side.

2(2n + 5) = 12 2n + 5 = 6 2n = 1 n = 1/2

2nd [CATALOG], solve( , enter equation, variable and guess after the bracket, close brackets with " ) ". You can also put lower and upper bounds after the guess.

NO!

Algebraically manipulate the equation until you have the indicated variable on one side of the equation and all of the other factors on the other side.

First, subtract 3x from each side of the equation. Then, divide each side of the equation by 7 .

There is no equation in the question, only an expression. An expression cannot be solved.

Brackets are used in maths to indicate the order of calculations in the equation.

To solve Boyle's Law equation for V2, first write the equation as P1V1 = P2V2. Then rearrange it to isolate V2 on one side, dividing both sides by P2 to solve for V2, which will be V2 = (P1 * V1) / P2.